Ionic liquid supported three-phase liquid-liquid-liquid microextraction as a sample preparation technique for aliphatic and aromatic hydrocarbons prior to gas chromatography-mass spectrometry - Basheer, C. (2014)
10.1016/j.chroma.2008.09.040